IZATIZONE AS INHIBITOR OF PLANT VIRUS INFECTION - А. В. Харіна; Т. Г. Кот; В. П. Поліщук; I. Є. Заєць; Н. В. Черватюк; А. I. Потопальський (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2009)
Izatizone was investigated for biocontrol efficiency against tobacco mosaic virus (TMV) in two model systems. The izatizone treatment of seeds and Nicotiana tabacum plants prior to inoculation with the virus enhanced plant growth and protected them against TMV that displayed in decrease of symptoms severity and reduction of virus quantity in plants. It was shown that investigated compound was capable of reducing the development of TMV in tissue culture and caused 21.7% reduction of virus quantity in callus.